Bahasa Serawai Sebagai Sarana Komunikasi Antarpribadi Di Desa Tanjung Menang - Doli Apriansa; Dilmai Putra; Aldila Vidianingtyas Utami (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This study aims to describe and analyze the role of the Serawai language as a means of interpersonal communication in Tanjung Menang Village, Seginim District, South Bengkulu Regency. This research employed a qualitative descriptive method, with data collected through observation, in-depth interviews, and documentation. The informants consisted of the village head, traditional leader, community members, and a university student selected using purposive sampling. Data analysis was conducted through data reduction, data display, and conclusion drawing based on Joseph A. DeVito’s interpersonal communication theory, which includes openness, empathy, supportiveness, positiveness, and equality. The findings indicate that the Serawai language is still actively used in family communication, traditional ceremonies, village meetings, and daily social interactions. The use of the Serawai language supports the creation of communication that is more open, empathetic, supportive, positive, and equal. It also functions as a cultural identity and social binder that strengthens relationships among community members. However, there is a tendency of decreasing use among younger generations due to modernization and the dominance of the Indonesian language. Therefore, collective efforts are needed to preserve the Serawai language as a cultural heritage and an effective means of interpersonal communication within the community.